The Effect of Using Papaya (Carica papaya L) Leaves on Blood Glucose and Growth Rate of Asian Seabass (Lates calcarifer) - Dasy , Ainayah Luthviani Sinun; Jasmanindar, Yudiana; Djonu, Asriati (International Journal of Educational and Life Sciences, 2024)
This research aims to determine the effect of using papaya (Carica papaya L) leaves on blood glucose and growth rate of Lates calcarifer. This research used a completely randomized design (CRD) with 4 treatments and 3 replications. Treatment A with the addition of papaya leaves powder (C. papaya) of 3.25 g/L, B of 3.75 g/L, C of 4,25 g/L and D as a Control or without the addition of papaya leaves. The parameters measured were blood glucose, absolute growth and survival. The best treatment is treatment A (C. papaya 3.25 g/L) which produced fish blood glucose on the 60th day of 90 mg/dL, 100% survival rate, absolute weight growth and length of 6.43 g and 6.20 cm. .